ANALISIS KEANDALAN SISTEM DISTRIBUSI 20 kV PENYULANG BUNUL PT. PLN ULP MALANG KOTA MENGGUNAKAN METODE RIA (RELIABILITY INDEX ASSESSMENT) - Farraz, Dayrry Yozza; Utomo, Teguh; Wijono, n/a (Jurnal Mahasiswa TEUB, 2024)
Abstract - This paper discusses the reliability analysis of the 20 kV distribution system of Bunul Feeder at PT. PLN ULP Malang Kota. Several indices used to measure the reliability level of the distribution system are SAIFI (System Average InterruptionFrequency Index), SAIDI (System Average Interruption Duration Index), and CAIDI (Customer Average Interruption DurationIndex). The objective of this research is to obtain the reliability index values (SAIDI, SAIFI, CAIDI) for the Bunul Feeder at PT. PLN ULP Malang Kota using the Reliability Index Assessment (RIA) method and single line diagram simulation on ETAP, as well as comparing these reliability index values with the SPLN 59 standard from 1985. The methods employed include the RIA method and ETAP 19.0.1 simulation software. Based on the RIA method calculations, the failure rate and unavailability values are2.7120210 interruptions/year and 12.3712701 hours/year, respectively. Meanwhile, SAIFI is 1.6761635 interruptions/year, SAIDI is 9.2354936 hours/year, and CAIDI is 5.5099002 hours/interruption. The simulation results for the reliability indices in ETAP show SAIFI, SAIDI, and CAIDI values of 2.4640 interruptions/year, 5.7485 hours/year, and 2.333 hours/interruption, respectively.Based on the results obtained, the percentage differences in the reliability index values of the RIA and ETAP methods for SAIFI, SAIDI, CAIDI respectively are 47%, 38%, 58%. The differences in values are caused by imperfect switching conditions in calculations involving components other than distribution channels. With all reliability index values from the RIA method and ETAP simulation for the Bunul Feeder of PT. PLN ULP Malang Kota being smaller than the values in SPLN 59 of 1985, the distribution system of the Bunul Feeder can be considered reliable. Keywords—Bunul feeder, reliability index, RIA method, ETAP, SPLN 59 of 1985